Integrasi Budaya Jawa dan Melayu dalam Praktik Jujuran Pernikahan pada Masyarakat Desa Sungai Kayu, Jambi - Setiawan, Agus (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research departs from the practice of jujuran marriage from the integration of Malay culture to Javanese culture that occurs in Sungai Kayu Aro Village, Senyerang District, Jambi Province. The purpose of this study is to find out how Javanese and Malay communities manage interactions in the practice of jujuran marriage and the dynamics of the integration of honesty marriage traditions in the Sungai Kayu Aro Village community in the perspective of legal interlegality. This type of research is field research, qualitative research methods, with a legal sociology approach. Data collection techniques are interviews, observation and documentation. The results of the study indicate that the integration of the jujuran tradition is a form of legal interlegality in carrying out Javanese and Malay marriages. Negotiations of different traditions occur so that they produce an agreement when the Javanese and Malay tribes marry, the traditions carried out are in accordance with the place where the wedding reception is held, the integration of the jujuran tradition which is a tradition of the Malay tribe adopted by the Javanese tribe from the results of the negotiation, as well as in the honesty tradition of the Sungai Kayu Aro Village community in carrying out community marriages not only follow one legal system but there is a combination of customary law, Islamic law, and national law so that the marriage of the Sungai Kayu Aro Village community reflects the occurrence of legal interlegality.